2015
DOI: 10.4236/wjnse.2015.53009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminium Doping on Structural and Magnetic Properties of Ni-Zn Ferrite Nanoparticles

Abstract: Aluminium doped Ni-Zn ferrite nanoparticles of general formula of Ni0.5Zn0.5AlxFe2−xO4 (x = 0.0, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0) have been synthesized by sol-gel auto combustion method and characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), Fourier transform spectroscopy (FTIR) and vibrating sample magneto meter (VSM). XRD studies confirm that all compositions show single phase cubic spinel structure. The crystallite size was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 34 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Increasing the Ni 2+ ion concentration together with Al 3+ ion substitution considerably lowers the saturation magnetization and leads to superparamagnetic behaviour. In our earlier work, we have observed superparamagnetism for the composition of Ni 0.5 Zn 0.5 Al x Fe 2-x O 4 at x = 2.0 [38].…”
Section: Magnetic Propertiesmentioning
confidence: 80%
“…Increasing the Ni 2+ ion concentration together with Al 3+ ion substitution considerably lowers the saturation magnetization and leads to superparamagnetic behaviour. In our earlier work, we have observed superparamagnetism for the composition of Ni 0.5 Zn 0.5 Al x Fe 2-x O 4 at x = 2.0 [38].…”
Section: Magnetic Propertiesmentioning
confidence: 80%
“…The powder exhibited clear hysteresis showing typical magnetic behavior, ferromagnetic, having a nonzero coercivity and remanance. It has been observed that narrow hysteresis loops show the characteristic of soft magnetic materials, which has much importance in magnetic memory purposes. From the magnetization data, parameters like saturation magnetization (1.667 emu g −1 ), coercivity (27.253 Oe), remanent magnetization (0.119 emu g −1 ), and squareness ratio (0.0713) are measured.…”
Section: Resultsmentioning
confidence: 99%
“…The distinct approaches presented in W-H analysis, we assume that size and strain broadening are additive components of the total integral breadth of a Bragg peak [28][29][30]. The distinct angle (θ) dependencies of both effects laid the basis for the separation of size and strain broadening in the analysis of Williamson and Hall [30][31].…”
Section: Williamson-hall Analysis and "Size-strain Plot"(ssp) Analysismentioning
confidence: 99%